Analisis Penerimaan Coretax Administrations System Dalam Aspek Pengguna Akhir - Pradnyadewi, I Dewa Ayu Agung (Universitas Prof.Hazairin,SH Bengkulu, 2025)
This study aims to examine the influence of Perceived Usefulness, Perceived Ease of Use, and Subjective Norms on Behavioral Intentions to Use the CoreTax Administration System, with System Reliability as a moderating variable on individual taxpayers in Denpasar City. This research was conducted in Denpasar City and focused on individual taxpayers registered with the Directorate General of Taxes (DGT). This study employed a quantitative approach with a survey method using a questionnaire. Data were analyzed using SmartPLS 4.0 with Structural Equation Modeling (SEM-PLS) techniques to test the relationships and moderating effects between variables. The results of the study indicate that Perceived Usefulness, Perceived Ease of Use, and Subjective Norms all have a positive influence on the intention to use the CoreTax Administration System. Furthermore, System Reliability strengthens the positive relationship between these three independent variables and Behavioral Intention, indicating that a more reliable system can increase users' willingness to adopt it.This study found that perceived usefulness, perceived ease of use, and subjective norms positively influenced behavioral intention to use the CoreTax system, which was strengthened by system reliability. These results support the digital tax adoption strategy, which emphasizes technology acceptance in the public sector.